The Illocutionary Frames Principle (IFP) and the Austinian Postulations: A Clause-structure Investigative Discourse (Global Journal of Human-Social Science, 2013)
Austin 1962 is a theory of speech act in this regard it is essentially a theory in pragmatics which as a field of language study studies how language is used according to varied contextual nuances In this paper my arguments subtly engage semantics and those pragmatic notions which constitute the communicative elements produced by clause structure I explore the System of Mood the Abstract Performative Hypothesis and the Illocutionary Frames Principle IFP to establish my positions The findings include the clause in which a speech act verb occurs determines illocutionary acts performed in discourse among other things linguistic issues abound which reveal the strengths and weaknesses of Austinian postulations apart from determining what is communicated in discourse clause structure also has effects and implications on meaning and participants
Keywords: pragmatics; semantics; mood; abstract performative hypothesis; illocutionary frames principle; emergent context; clause structure; speech act; implica